Meta-Analisis Komparasi Contextual Teaching and Learning dan Pembelajaran Konvensional - Samritin Samritin (Departement of Mathematics Education, 2021)
Contextual Teaching and Learning (CTL) is a learning approach adopted from the United States that began to be implemented in Indonesia starting around the 2000s. Since then, there have been many studies examining the effectiveness of CTL compared to other approaches, one of which is the conventional approach. This study examines the results of comparative studies using meta-analysis. The aim was to describe the significance of CTL's effectiveness compared to conventional approaches by analyzing the effect sizes of 16 published studies. The studies analyzed were obtained from search results using the Publish or Parish application. The 16th study was obtained using the Google Scholar index with the criteria for the publication period of 2014 - 2019, the study contained the sample size, mean, standard deviation or variance of the experimental and control classes. The effect size and standard error of each study were analyzed using MS Excel. Furthermore, heterogeneity testing and combined effect size were analyzed using the JASP application. Based on the results of data analysis using a significance level of α = 0.05, Q = 0.388 was obtained with a p-value = 1.000. This shows that the effect sizes of the 16 studies analyzed are homogeneous or not heterogeneous. Based on the results of data analysis, an effect size of 0.106 was also obtained with a p-value of 0.692 at the 95% confidence level. The effect size is in the weak and insignificant category. Therefore it is concluded that the effectiveness of the application of CTL is not significant compared to the conventional approach.This could be due to the small effect size of some studies. In addition, studies that have large effect sizes also have large standard errors. This finding has implications for increasing teacher competence in implementing CTL.